Investigação da tolerância de Borreria latifolia (Aubl) e Richardia brasiliensis (Gomes) a Glyphosate e competitividade com a cultura da soja - Diesel, Francielli (2016)
Herbicide tolerant weed species are widely disseminated in all Brazilian regions. The objective of this research was to increase the information about the glyphosate tolerance on species / biotypes of the family Rubiaceae, allowing a better understanding of the physiological and genetic mechanisms associated to the tolerance and the soybean losses caused due to interference. Populations of Borreria latifolia and Richardia brasiliensis were sampled in the States of Paraná and Santa Catarina. The first study, which evaluated the response to doses of glyphosate in these species / populations, was conducted in a completely randomized design (DIC) in a bifactorial scheme, with the first factor being the populations of each species (B. latifolia and R. brasiliensis), and the second the glyphosate level (0, 74, 163, 360, 792 and 1742 g ha-1 of ea). Visual control at 14 and 28 days after application (DAA), green aerial part mass (MPAV) and dry matter (MPAS) at 28 DAA were evaluated. The investigation of the absorption and translocation with radiophase (14C) -labeled glyphosate was conducted in DIC, with three replicates, in a bifactorial scheme, being the first factor species / biotypes with a glyphosate response and the second factor seven periods of evaluation (2,8 , 24, 48 and 72 hours after application with the herbicide (HAA). Two studies were carried out in greenhouse, in DIC to quantify epicuticular waxes present on the surface of the leaves of the rubiaceous species. The first one was arranged in a 6 x 2 factorial scheme, with six biotypes, three of B. latifolia and three of R. brasiliensis (sensitive, medium tolerance and high tolerance for each species) submitted to the regimes near soil field capacity (CC) and near the permanent wilting point (PMP). Subsequently, the epicuticular waxes were extracted with solvents and quantified by weighing. The second factor was arranged in factorial 2 x 3 x 5, the first factor being the soil water conditions (CC and PMP), the second factor three biotypes with contrasting responses to glyphosate and the third factor doses of the glyphosate herbicide 0, 72, 163, 360 and 792 g and ha-1. The plants control levels were determined at 14 and 28 DAA, MPAV and MPAS at 28 DAA. Another study determined the genetic variability among individuals and populations of B. latifolia and R. brasiliensis species with different responses to the herbicide glyphosate (sensitive and with greater tolerance) using the RAPD technique. Two studies conducted in a randomized complete block design with four replications, in a two - factorial scheme to determine the competitive capacity of rubiaceous species with soybean culture. The first factor consisted of the species B. latifolia and R. brasiliensis and the second by the plant density (0, 2, 4, 6, 8, 10 and 12 plants m-2). Plant height, leaf area and total chlorophyll in the V6 and R5 stages of the crop, number of pods per plant, number of grains per pod, mass of 1000 grains and loss of grain yield were evaluated. There was variability of response to glyphosate among the biotypes of B. latifolia and R. brasiliensis species collected in different locations of Paraná and Santa Catarina. Most of the absorbed herbicide was deposited on the treated leaf, with the highest translocation in the sensitive biotype only in the 48 and 72 HAA evaluations. The production of epicuticular waxes was increased by water deficit, with greater emphasis on glyphosate tolerant biotypes for both species. The RAPD markers were satisfactory in detecting polymorphism among individuals belonging to B. latifolia and R. brasiliensis biotypes with contrasting responses to glyphosate herbicide. The species B. latifolia was more competitive with the soybean crop, compared to R. brasiliensis, causing higher losses in all variables.